Managerial Conflicts in Management Psychology and Institutional Economics - T. A. Lignovskaya; B. A. Erznkyan (Управление)
The authors proceed from the fact that while teaching the management psychology to students which are already familiar with the institutional economics foundations, it is useful to give them information enable to draw parallels between these two academic disciplines that will help the students become more familiar not only with each of these academic disciplines, but also more vividly present themselves problems emerging in management. In this paper a comparison of typical cases from the management psychology and institutional economics is carrying out on the example of managerial conflicts.